Genetic stability of Brucella abortus isolates from an outbreak by multiple-locus variable-number tandem repeat analysis (MLVA16) - Dorneles, Elaine Maria Seles (BioMed Central, 2014)
BACKGROUND: Brucellosis caused by Brucella abortus is one of the most important zoonoses in the world. Multiple-locus variable-number tandem repeat analysis (MLVA16) has been shown be a useful tool to epidemiological traceback studies in B. abortus infection. Thus, the present study aimed (i) to evaluate the genetic diversity of B. abortus isolates from a brucellosis outbreak, and (ii) to investigate the in vivo stability of the MLVA16 markers. RESULTS: Three-hundred and seventy-five clinical samples, including 275 vaginal swabs and 100 milk samples, were cultured from a brucellosis outbreak in a cattle herd, which adopted RB51 vaccination and test-and-slaughter policies. Thirty-seven B. abortus isolates were obtained, eight from milk and twenty-nine from post-partum/abortion vaginal swabs, which were submitted to biotyping and genotyping by MLVA16. Twelve B. abortus isolates obtained from vaginal swabs were identified as RB51. Twenty four isolates, seven obtained from milk samples and seventeen from vaginal swabs, were identified as B. abortus biovar 3, while one isolate from vaginal swabs was identified as B. abortus biovar 1. Three distinct genotypes were observed during the brucellosis outbreak: RB observed in all isolates identified as RB51; W observed in all B. abortus biovar 3 isolates; and Z observed in the single B. abortus biovar 1 isolate. Epidemiological and molecular data show that the B. abortus biovar 1 genotype Z strain is not related to the B. abortus biovar 3 genotype W isolates, and represents a new introduction B. abortus during the outbreak. CONCLUSIONS: The results of the present study on typing of multiple clinical B. abortus isolates from the same outbreak over a sixteen month period indicate the in vivo stability of MLVA16 markers, a low genetic diversity among B. abortus isolates and the usefulness of MLVA16 for epidemiological studies of bovine brucellosis.